2013
DOI: 10.1039/c3ee40600h
|View full text |Cite
|
Sign up to set email alerts
|

Novel cobalt/nickel–tungsten-sulfide catalysts for electrocatalytic hydrogen generation from water

Abstract: Broader contextGreat efforts are being focused to search for viable electrocatalysts for the water oxidation reaction (WOR) and the hydrogen evolution reaction (HER) which are preferably composed of only earth-abundant-elements. We report herein two novel ternary suldes, cobalt/nickel-tungsten-suldes, as attractive alternatives to platinum electrocatalysts for the HER. These suldes are easily electrodeposited on conducting electrodes from an aqueous solution of readily available precursors. Implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 42 publications
8
136
0
Order By: Relevance
“…39,40 A number of highly active amorphous HER catalysts are recently developed using electrochemical deposition methods similar to the one developed for the deposition of amorphous molybdenum sulfide film catalysts. [41][42][43] Tram et al reported the electrodeposition of ternary sulfides of cobalt-tungsten and nickel-tungsten which showed good HER activity. 42 Wang et al reported a simple, one-step electrochemical copolymerization method to fabricate a hybrid film containing polypyrrole (PPy), a conductive polymer, and amorphous molybdenum sulfide catalyst.…”
Section: Related Synthesis and Application Of Amorphous Molybdenum Sumentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 A number of highly active amorphous HER catalysts are recently developed using electrochemical deposition methods similar to the one developed for the deposition of amorphous molybdenum sulfide film catalysts. [41][42][43] Tram et al reported the electrodeposition of ternary sulfides of cobalt-tungsten and nickel-tungsten which showed good HER activity. 42 Wang et al reported a simple, one-step electrochemical copolymerization method to fabricate a hybrid film containing polypyrrole (PPy), a conductive polymer, and amorphous molybdenum sulfide catalyst.…”
Section: Related Synthesis and Application Of Amorphous Molybdenum Sumentioning
confidence: 99%
“…[41][42][43] Tram et al reported the electrodeposition of ternary sulfides of cobalt-tungsten and nickel-tungsten which showed good HER activity. 42 Wang et al reported a simple, one-step electrochemical copolymerization method to fabricate a hybrid film containing polypyrrole (PPy), a conductive polymer, and amorphous molybdenum sulfide catalyst. The hybrid system exhibited a remarkable HER activity.…”
Section: Related Synthesis and Application Of Amorphous Molybdenum Sumentioning
confidence: 99%
“…[1] Owing to thermodynamic convenience and potential application in proton-exchange membrane or alkaline electrolyzers,most effort in this field has been devoted to developing HER catalysts for strongly acidic conditions and OER catalysts for strongly basic conditions.T ransition-metal sulfides,s elenides,p hosphides,c arbides,b orides,a nd even non-metal materials have shown catalytic performance for HER in strong acidic electrolytes,such as MoS 2 , [2] M-MoS 2 , [3] Co/Ni-WS x , [4] MS 2 and MSe 2 (M = Fe,C o, Ni, etc. ), [5] FeS, [6] CoS, [7] Ni 3 S 2 , [8] MoC and MoB, [9] MoP, [10] WP and WP 2 , [11] CoP and Co 2 P, [12] Ni 2 P, [13] FeP, [14] andC u 3 P. [15] On theo ther hand, many OER catalysts based on the oxides/hydroxides of cobalt, [16] nickel, [17] manganese, [18] iron, [19] and copper [20] have also been reported with OER catalytic activities under basic conditions.H owever,t oa ccomplish overall water splitting, the coupling of HER and OER catalysts in the same electrolyte is desirable.T he current prevailing approaches often result in incompatible integration of the two catalysts and lead to inferior overall performance.I tr emains ag rand challenge to develop bifunctional electrocatalysts active for both HER and OER.…”
mentioning
confidence: 99%
“…[29,89,[269][270][271] Due to the unsaturated sites on the surface, electrocatalysts with amorphous structure were found to expose more active sites for electrochemical reactions than their crystalline counterparts. [272][273][274] A pioneering work was reported by Merki et al, in which amorphous ternary MMoS x (M = Fe, Co, and Ni) films were electrodeposited from aqueous solutions containing (NH 4 ) 2 MoS 4 and MCl 2 .…”
Section: Amorphous M-mo(w)-s (M = Fe Co and Ni)mentioning
confidence: 99%
“…[28,30,75,79,82,83,87] When synthesizing Mo-or W-containing MMSs using these solutionbased methods, (NH 4 ) 2 Mo(W)S 4 is generally used as both Mo(W) and S sources. [29,48,63,89] The gas sulfidation method is another facile approach to synthesize MMSs. This method involves the synthesis of various template precursors and subsequent sulfidation with H 2 S or S vapor.…”
Section: Wwwadvenergymatdementioning
confidence: 99%